2000
DOI: 10.1054/bjoc.1999.1039
|View full text |Cite
|
Sign up to set email alerts
|

Decreased GTPase activity of K- ras mutants deriving from human functional adrenocortical tumours

Abstract: Our previous studies have shown that seven out of 15 patients with adrenocortical tumours contained K- ras gene mutation. In addition, the mutation type was a multiple-site mutation, and the hot spots were located at codons 15, 16, 18 and 31, which were different from those reported before (codons 12, 13 and 61). To understand whether the mutation hot spots in human adrenocortical tumours were associated with activation of K- Ras oncogene and the alterations of its biocharacteristics, mutant K- Ras genes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Then, a membrane array blotted with these 22 gene probes was constructed and applied to test the peripheral blood samples from patients with various cancers. The results demonstrated that the K-ras oncogene membrane array had a remarkable potential to detect activated K-ras in human cancers (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 91%
“…Then, a membrane array blotted with these 22 gene probes was constructed and applied to test the peripheral blood samples from patients with various cancers. The results demonstrated that the K-ras oncogene membrane array had a remarkable potential to detect activated K-ras in human cancers (14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 91%
“…The oligonucleotides used to amplify a fragment of human c-raf-1 were 5'-CACAGATGGATCCAAGACAAGCAACAC-3' and 5'-GGG-AAGAAT-TCACAGGAAATCTAC-3' (Herrmann et al, 1995) cDNA. The resulting 412-base pair fragment was cleaved with BamHI and EcoRI, purified, and cloned into the GST fusion vector pGEX-4T-2 (Amersham, Pharmacia Biotech UK, Ltd) as described previously (Lin et al, 2000). The resulting plasmid, pGEX-RBD, was transformed into E. coli strain TG1.…”
Section: Construction Of Gst-rbd Of Raf-1 Expression Plasmidmentioning
confidence: 99%
“…300 mM b-mercaptoethanol). The protein samples were separated on vertical slab gels composed of 10% polyacrylamide containing 0.1% sodium dodecyl sulphate (SDS) prepared in 3 mM Tris-HCl, pH 8.8, as described previously (Lin et al, 2000). Following electrophoresis, the protein was electroblotted to a nitrocellulose membrane (Schleicher & Schusll GmbH, Dassel, Germany).…”
Section: Precipitation and Immunoblot Of Active Form Rasgtp By Gst-rbmentioning
confidence: 99%
“…1,2,5,9 Additionally, mutations occur at codons 15,16,18, and 31. 24,25 These mutations result in abrogation of normal intrinsic or GAP-stimulated GTPase activity of RAS, leading to increased half-lives of mutant RAS-GTP. 5,9,26 Transformation results, at least in part, from deregulated stimulation of mitogenic signal transduction pathways.…”
Section: Introductionmentioning
confidence: 99%